The reform of section 103(1) - Nunes, Tony (Department of Commercial Law, 2024)
With the increasing taxation burden that is placed on the citizens of the modern state, the practice has grown for those who are aggrieved by their share of the tax burden to try to reduce it. The methods adopted by those daring enough to challenge the revenue authorities have not always been favourably received and have even been considered improper or "evil", as, it is argued, the tax burden is shifted from those who avoid tax to those who, by reason of lack of access to skilled advice, or because their income is not readily susceptible to tax saving devices, must accept the demands of the Receiver of Revenue. Additionally, the resultant revenue that the State loses from these tax avoidance schemes, is presumably made up by placing a heavier burden on the shoulders of the innocent. Thus the State has taken steps to ensure that tax avoidance schemes do not subvert the Receiver's ability to collect each citizen's fair share of the tax burden. This is achieved either by plugging each hole as it appears in the taxing legislation or by enacting a general anti-avoidance provision, supported by legislation covering specific areas of tax avoidance. Each method merely empowers the revenue authority to disregard the avoidance scheme used by the taxpayer and to regain the tax lost through the taxpayer's use of the scheme. The determination and ingenuity of the taxpaying public is renowned and inevitably a new tax avoidance scheme evolves challenging the limits of the legislation.